2016
DOI: 10.1186/s12884-016-1033-6
|View full text |Cite
|
Sign up to set email alerts
|

Coverage, compliance, acceptability and feasibility of a program to prevent pre-eclampsia and eclampsia through calcium supplementation for pregnant women: an operations research study in one district of Nepal

Abstract: BackgroundCalcium supplementation during pregnancy has been shown to reduce the incidence of pre-eclampsia/eclampsia among women with low calcium intake. Universal free calcium supplementation through government antenatal care (ANC) services was piloted in the Dailekh district of Nepal. Coverage, compliance, acceptability and feasibility of the intervention were evaluated.MethodsAntenatal care providers were trained to distribute and counsel pregnant women about calcium use, and female community health volunte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…Of note, 6 studies were RCTs, 21 , 22 , 23 , 24 , 25 , 26 and 6 more were nonrandomized controlled, that is, cluster-controlled 27 , 28 , 29 , 30 or were before and after studies. 31 , 32 In addition, 9 were cohort studies, 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 2 were cross-sectional, 42 , 43 1 was a pure qualitative study 44 , and another had cluster-controlled and qualitative elements. 45 Notably, 15 of the studies involved community-based interventions, 22 , 23 , 26 , 27 , 28 , 29 , 31 , 34 , 36 , 37 , 38 , 39 , 40 , 44 , 45 9 were hospital-based, 21 , 24 , 25 , 30 , 32 , 33 , 35 , 42 , 43 , and 1 contained elements of both.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, 6 studies were RCTs, 21 , 22 , 23 , 24 , 25 , 26 and 6 more were nonrandomized controlled, that is, cluster-controlled 27 , 28 , 29 , 30 or were before and after studies. 31 , 32 In addition, 9 were cohort studies, 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 2 were cross-sectional, 42 , 43 1 was a pure qualitative study 44 , and another had cluster-controlled and qualitative elements. 45 Notably, 15 of the studies involved community-based interventions, 22 , 23 , 26 , 27 , 28 , 29 , 31 , 34 , 36 , 37 , 38 , 39 , 40 , 44 , 45 9 were hospital-based, 21 , 24 , 25 , 30 , 32 , 33 , 35 , 42 , 43 , and 1 contained elements of both.…”
Section: Resultsmentioning
confidence: 99%
“… 45 Notably, 15 of the studies involved community-based interventions, 22 , 23 , 26 , 27 , 28 , 29 , 31 , 34 , 36 , 37 , 38 , 39 , 40 , 44 , 45 9 were hospital-based, 21 , 24 , 25 , 30 , 32 , 33 , 35 , 42 , 43 , and 1 contained elements of both. 41 The detailed summaries of the included studies can be found in Table 4 . The types of interventions reported in the included studies are shown in Figure 2, and the study locations are shown in Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Similar to IFA, a key limiting factor will be availability and accessibility of calcium supplements. Experience from Nepal reiterates the need for strengthening supply‐side factors including provision of complete ANC services and uninterrupted provision of supplements, which were associated with consumption of full‐course of calcium among PW who received them (Thapa et al, ). Consistent with literature, our study shows that maternal knowledge, receiving counselling on calcium supplementation, beliefs and self‐efficacy, ANC visits, and positive social norms were associated with increased consumption of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…In the developing world, pregnant women are willing to take calcium, oral iron and micronutrients. 19–21 If instructed about potential side-effects and reminded frequently, women had higher levels of adherence with the greatest barrier being forgetfulness. Average medication adherence in pregnancy for chronic illness is higher than for non-routine medications at 90%–95%, 22 hence it its promising that we have noted a rate as high as this in our own study.…”
Section: Discussionmentioning
confidence: 99%